Growth Responses of Alpukat (Persea americana Mill.) Var. YM to the Application of Vitamin B1 and Banana Leaf Litter Compost - Ismi Auliathul Husna; Susiyanti; Zahratul Millah; Endang Sulistyorini (Jurusan Budidaya Perkebunan, 2024)
YM avocado is a superior product from Lebak, Banten, which requires sustainable cultivation for optimal growth. This study aims to improve the growth of YM avocado by applying vitamin B1 and banana leaf compost using a two-factor group randomized design. Data were analyzed using ANOVA, DMRT at the 5% level, and linear regression analysis. The factors were vitamin B1, with doses of 0, 15, 30, and 45 mg/l, and banana leaf compost, with doses of 0, 125, and 250 g/plant. The provision of vitamin B1 at a dose of 45 mg/l gave the highest growth results in the parameters of the number of leaves, leaf length-width ratio, plant height, leaf area, and leaf chlorophyll content, while the stem diameter showed the highest growth at a dose of 15 mg/l. Giving banana leaf compost at a dose of 250 gr/plant gave the highest growth in plant height, number of leaves, leaf area, and leaf chlorophyll content, while the dose of 125 gr/plant gave the highest growth in stem diameter parameters. It can be concluded that the provision of vitamin B1 and banana leaf compost can increase the growth of YM avocado plants.